Proceedings of the 4th International Conference on Sport Science, Health, and Physical Education (ICSSHPE 2019) 2020
DOI: 10.2991/ahsr.k.200214.041
|View full text |Cite
|
Sign up to set email alerts
|

Increasing the Mental Toughness Through Match Simulations in a Basketball Game

Abstract: In the current era, team sports are very popular and become the centre of attention. One of the most popular sports, both internationally and domestically, is basketball. Basketball not only supports physical training, but also must support tactical training. In general, mental toughness is a general term used by most athletes, coaches, and the media to understand mental characteristics that excel in training and competition. One method to improve mental toughness in basketball athletes is match simulation. Co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…On the second theme, identifying the effects of the recognized limitations yields poor performance as gathered data information both from IDI and FGD. Insufficient physical training [35], academic stress [24,36], lack of psychological well-being [36], lack of mental toughness [37] criticism [38], negative feedback, and lack of mentoring time [39] are some of the compounded regulations that need to be addressed effectively and efficiently. In order to counter the recognized problems, [40] found that self-assessment is the key to unlock the self-determination and self-efficacy of adolescent athletes in the environment of competitive sports.…”
Section: Discussionmentioning
confidence: 99%
“…On the second theme, identifying the effects of the recognized limitations yields poor performance as gathered data information both from IDI and FGD. Insufficient physical training [35], academic stress [24,36], lack of psychological well-being [36], lack of mental toughness [37] criticism [38], negative feedback, and lack of mentoring time [39] are some of the compounded regulations that need to be addressed effectively and efficiently. In order to counter the recognized problems, [40] found that self-assessment is the key to unlock the self-determination and self-efficacy of adolescent athletes in the environment of competitive sports.…”
Section: Discussionmentioning
confidence: 99%
“…In line with this, experts have reported that mental toughness can moderate stress, help regain balance after failure, and encourage mobilization (Zalewska et al, 2019). Various ways can be done to increase mental toughness in individuals, one of which is by remaining active in sports (Sartika et al, 2020;Tibbert, 2013).…”
Section: Introductionmentioning
confidence: 96%